Role of Polar Amplification in Long-Term Surface Air Temperature Variations and Modern Arctic Warming - Bekryaev, Roman V.; Polyakov, Igor V.; Alexeev, Vladimir A. (Journal of climate, 2010)
This study uses an extensive dataset of monthly surface air temperature (SAT) records (including previously unutilized) from high-latitude (>60°N) meteorological land stations. Most records have been updated by very recent observations (up to December 2008). Using these data, a high-latitude warming rate of 1.36°C century−1is documented for 1875–2008—the trend is almost 2 times stronger than the Northern Hemisphere trend (0.79°C century−1), with an accelerated warming rate in the most recent decade (1.35°C decade−1). Stronger warming in high-latitude regions is a manifestation of polar amplification (PA). Changes in SAT suggest two spatial scales of PA—hemispheric and local. A new stable statistical measure of PA linking high-latitude and hemispheric temperature anomalies via a regression relationship is proposed. For 1875–2008, this measure yields PA of ∼1.62. Local PA related to the ice–albedo feedback mechanisms is autumnal and coastal, extending several hundred kilometers inland. Heat budget estimates suggest that a recent reduction of arctic ice and anomalously high SATs cannot be explained by ice–albedo feedback mechanisms alone, and the role of large-scale mechanisms of PA of global warming should not be overlooked.